POP1 inhibits MSU-induced inflammasome activation and ameliorates gout - de Almeida, Lucia; Devi, Savita; Indramohan, Mohanalaxmi; Huang, Qi-Quan; Ratsimandresy, Rojo A.; Pope, Richard M.; Dorfleutner, Andrea; Stehlik, Christian (Frontiers in Immunology, 2022)
Canonical inflammasomes are innate immune protein scaffolds that enable the activation of inflammatory caspase-1, and subsequently the processing and release of interleukin (IL)-1, IL-18, and danger signals, as well as the induction of pyroptotic cell death. Inflammasome assembly and activation occurs in response to sensing of infectious, sterile and self-derived molecular patterns by cytosolic pattern recognition receptors, including the Nod-like receptor NLRP3. While these responses are essential for host defense, excessive and uncontrolled NLRP3 inflammasome responses cause and contribute to a wide spectrum of inflammatory diseases, including gout. A key step in NLRP3 inflammasome assembly is the sequentially nucleated polymerization of Pyrin domain (PYD)- and caspase recruitment domain (CARD)-containing inflammasome components. NLRP3 triggers polymerization of the adaptor protein ASC through PYD-PYD interactions, but ASC polymerization then proceeds in a self-perpetuating manner and represents a point of no return, which culminates in the activation of caspase-1 by induced proximity. In humans, small PYD-only proteins (POPs) lacking an effector domain regulate this key process through competitive binding, but limited information exists on their physiological role during health and disease. Here we demonstrate that POP1 expression in macrophages is sufficient to dampen MSU crystal-mediated inflammatory responses in animal models of gout. Whether MSU crystals are administered into a subcutaneous airpouch or into the ankle joint, the presence of POP1 significantly reduces neutrophil infiltration. Also, airpouch exudates have much reduced IL-1 and ASC, which are typical pro-inflammatory indicators that can also be detected in synovial fluids of gout patients. Exogenous expression of POP1 in mouse and human macrophages also blocks MSU crystal-induced NLRP3 inflammasome assembly, resulting in reduced IL-1 and IL-18 secretion. Conversely, reduced POP1 expression in human macrophages enhances IL-1 secretion. We further determined that the mechanism for the POP1-mediated inhibition of NLRP3 inflammasome activation is through its interference with the crucial NLRP3 and ASC interaction within the inflammasome complex. Strikingly, administration of an engineered cell permeable version of POP1 was able to ameliorate MSU crystal-mediated inflammation in vivo, as measured by neutrophil infiltration. Overall, we demonstrate that POP1 may play a crucial role in regulating inflammatory responses in gout.